CHOLESTEROL LOWERING EFFECT OF CHITOSAN NANOPARTICLES USING PARIJOTO FRUITS EXTRACT - Fania Putri Luhurningtyas; Rissa Laila Vifta; Nur Syarohmawati; Mahardika Adhi Candra (Sanata Dharma University, 2020)
Parijoto (Medinilla speciosa Reinw. ex Blum) fruit is known to have pharmacological activity as cholesterol lowering levels. Its activity needs to be increased with nanoparticle system so that the active substance can bind 100% to the action target. This study aims to determine the formation of nanoparticles from parijoto fruit (NEBP) and activity test as a decrease in cholesterol levels. The formation of nanoparticles used variations of concentration and volume of chitosan and NaTPP. Anti-cholesterol testing is based on the amount of free cholesterol in the sample that reacted with Lieberman-Burchard into complex green compounds. The best formation of NEBP was 0.2% chitosan, 0.1% NaTPP and volume ratio 5:1. The particle size showed an average size of 269.3 nm (10-1000 nm). The result of the percent transmittance and polydispersity index were 99,379 (close to 100%) and 0.378 (PDI 0.5). The functional group-specific of NEBP was OH, N-H, PO3. The morphology was round and non-uniform particles. NEBP can decrease 50% cholesterol levels with a smaller EC50 value was 89.08 compared to the extract (EC50 259.98 ppm). Nanoparticles of parijoto fruit is a potential candidate for anti-cholesterol drug.